Determining the levels of daily climatic comfort for humans in the eastern region of the Kingdom of Saudi Arabia for the period from 1985-2012 - Al-Jeban, Sarah Abdullah Mohammed (Journal of Humanities & Social Sciences, 2022)
Climate plays an important and essential role in the lives of the residents of the eastern region, and its impact is reflected on their health, activity and climatic comfort. and Hofuf) to highlight the most appropriate times that allow a person to achieve efficiency in his work and increase his production in quantity and quality, and to engage in tourism activity with climatic safety, This study aims to determine climatic comfort levels, highlight temporal and spatial differences in human climatic comfort indicators based on daily averages of temperature and relative humidity, and determine the impact of wind speed and direction on human climatic comfort levels, based on empirical equations such as the application of Oliver’s equation using average daily temperatures daily average relative humidity; To determine the levels of daily human climatic comfort, as well as using some statistical methods to determine the degrees of difference between coastal and inland cities. The results of the study led to determining the time periods in which the values of daily human climatic comfort levels are comfortable, or relatively comfortable, to benefit from them in activating various human activities, whether productive or recreational. In the city of Qaisumah, these periods extend between the first day of January and until today. The fifteenth of May, as well as the period from the twenty-sixth of September to the thirty-first of December, and the city of Dhahran from the first day of January to the twenty-ninth of April, As well as from the first day of November until the thirty-first day of December, and as for the city of Hofuf, periods of relative comfort and comfort extend between the first day of January until the twenty-seventh day of April, as well as the period from the eighteenth day of October until The thirty-first day of December.